2010
DOI: 10.1584/jpestics.r10-08
|View full text |Cite
|
Sign up to set email alerts
|

Environmental applications of earthworm esterases in the agroecosystem

Abstract: Chemical control of pests is still necessary in agriculture, despite the growing efforts to introduce biocontrolbased strategies. Many studies have evidenced the harm of pesticide side-effects on natural populations of pest enemies and other non-target organisms. Moreover, pesticide-contaminated soils can act as a secondary pollution source causing contamination in environmental compartments of critical concern to public health (water resource). These environmental risks need to be assessed and monitored for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 116 publications
1
11
0
Order By: Relevance
“…132) Their activity in the post-mitochondrial fraction is generally examined by spectrophotometrically monitoring hydrolysis product of a phenyl (thio) acetate derivative. Fenitrothion (E. fetida), 133) pirimiphosmethyl and deltamethrin (E. andrei), 134) and dimethoate (E. 135) significantly decreased the CaE activity in the paper contact test.…”
Section: Esterasesmentioning
confidence: 99%
“…132) Their activity in the post-mitochondrial fraction is generally examined by spectrophotometrically monitoring hydrolysis product of a phenyl (thio) acetate derivative. Fenitrothion (E. fetida), 133) pirimiphosmethyl and deltamethrin (E. andrei), 134) and dimethoate (E. 135) significantly decreased the CaE activity in the paper contact test.…”
Section: Esterasesmentioning
confidence: 99%
“…The primary physiological role of BChE is not completely clear, but some studies suggest that this enzyme may play an important role in the hydrolysis of acetylcholine at cholinergic synapses like AChE (Kristoff et al 2012). Also, BChE could play a protective role in anticholinesterase intoxication by removing the pesticide prior to reaching the target site AChE and contribute to the sensitivity of the species to anticholinesterase pesticides (Sanchez-Hernandez 2007). A number of studies have been performed to urge ChE as a biomarker for prediction of OPs in aquatic invertebrates (Day and Scott 1990;Monserrat et al 1997;Chang et al 2006;Frasco et al 2006;Liu et al 2012;Rivadeneira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that the highly toxic oxon metabolites had a greater affinity for carboxylesterases (CEs) than their parent compounds. 29 However, the in vitro AChE system was not able to oxidatively desulfurize the P = S moiety. Consequently, the affinity for the active site of AChE was lower for the enantiomers of fensulfothion in the in vitro system.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorothioate‐type organophosphate insecticides such as fensulfothion need to be bioactivated by monooxygenases. A previous study has shown that the highly toxic oxon metabolites had a greater affinity for carboxylesterases (CEs) than their parent compounds . However, the in vitro AChE system was not able to oxidatively desulfurize the P = S moiety.…”
Section: Discussionmentioning
confidence: 99%